MEDIA DAN PRODUKSI BUDAYA - Amirudin, Amirudin (Fakultas Ilmu Budaya Universitas Diponegoro, 2016)
This article discusses the theoretical study of media and cultural production to fill the void in the perspective of media study in the anthropology perspective. This study is focused on how anthropology contributes to the development of media study in relation with the cultural formation. Through the study of Mazzarella‟s thought (2004) on the concept of mediated culture, and Bourdieu‟s thought (1993, 2005) and Turner‟s thought (1974) on the concept of domain (field), this article presents a new idea on how both thoughts are applied in the media study.